Dietary n-9, n-6 and n-3 fatty acids modulate the oxidative stress in brain and liver of mice: Effect of trans fatty acids supplementation - Lavandera, Jimena Veronica (2021)
BACKGROUND: Arachidonic (20:4n-6) and docosahexaenoic (22:6n-3) acids interaction affects brain structure and function. Unsaturated fatty acids (UFAs) generate oxygenated lipid-derived eicosanoids which modulate the inflammatory response. The presence of trans fatty acids (TFA) in neuronal membranes can favor to generation of pro-oxidant metabolites. OBJECTIVE: This study evaluated the effect of supplementation with TFA to diets containing different proportions of FA, on the oxidative stress (OS) generation and the inflammatory response in mice brain and liver. METHODS: CF1 mice were fed diets (16 weeks) with olive (O), corn (C) or rapeseed (R) oils. OS parameters and gene expression of some key liver and brain enzymes involved in OS production were evaluated. RESULTS: In brain and liver, lipoperoxidation was increased and catalase activity was decreased in C. In brain, glutathione was diminished by supplementation with TFA in all diets and histological sections showed lymphocytes in O and C. In liver, decreased amount of lipid vacuoles and increased of cyclooxygenase-1 (COX-1) and PPARγ mRNA levels were observed in R and Rt. IL-1b and IL-6 in serum were augmented in O and Ot. CONCLUSIONS: Rapeseed oil could have protective effects on the development of OS and inflammation, while TFA supplementation did not showed marked effects on these parameters.